The Anatomy of a Credit Supply Shock: Evidence from an Internal Credit Market - Liberti, José María; Sturgess, Jason (Journal of Financial and Quantitative Analysis, 2018)
We investigate how financial contracting interacts with lending-channel effects by tracing the anatomy of a credit supply shock using micro-level data from a multinational bank. Borrowers with stronger lending relationships, higher nonlending revenues, and those that pledge collateral, especially outside assets and real estate, experience less credit rationing. Consistent with a tightening of financing constraints post shock, borrower composition shifts toward larger and less risky firms, and loans exhibit higher collateralization rates. Our analysis highlights the value of relationships and suggests that relationship banking is a channel through which borrowers can mitigate lending-channel effects.